KARYA ALLAH DALAM MENJAMIN KESELAMATAN ORANG PERCAYA DALAM PERJANJIAN BARU - Suwito, Gregorius (Sekolah Tinggi Teologi Kristus Alfa Omega, 2017)
The debate is occurring among God's servants and academic theology schools about the assurance of salvation. This debate is represented Â by the teachings of Calvinism, Armenianism and the teachings of Lordship Salvation. It is hoped that this research Â can explain systematically and comprehensively about God's acts that guarantee the salvation of believers. To achieve its objectives this study uses the following steps: first, Collect passages in the NT relating to the topic to be studied. Second, Synthesizing phrases is difficult to find the right meaning. Thirdly, systematically recapitulate what the NT teaches about God's work in ensuring the salvation of believers. There is no reason for a new born person to live in doubt as to the certainty of his salvation. The born- again Christian will love holiness and hate sin. He must always rely on the Holy Spirit to help him in the process of growing up and putting flesh (Rom. 8:13). He must believe in God's triumphant promises as described above. He must depend entirely upon the Holy Spirit to live victoriously.